Application of Biochar Derived from Pomelo Peels and Corn Cobs for the Removal of Ammonium Residue in Wastewater after Distillation Process - Van Son, Tran; Duc Manh, Lai; Manh Khai, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
T his study aimed to utilize agricultural by-products to produce adsorbents that are capable of removing ammonium from the effluent after the distillation-based treatment of industrial wastewater. Pomelo peel and corn cobs were processed through multiple steps including H 3 PO 4 and pyrolysis to fabricate CC-Biochar and PP-Biochar materials for ammonium removal from water. The fabricated adsorbents exhibited a porous and heterogeneous surface structure, in which the walls of larger pores contained many smaller pores. CC-Biochar activated carbon had a more porous surface structure and more cavities than PP-Biochar activated carbon. Both CC-Biochar and PP-Biochar contained functional groups such as –C–O, C=C, C=O, C=N, C–H, –OH, and –NH. The optimal dosage of the modified adsorbents BioP-1 and BioP-2 was determined to be 10 g/L, corresponding to the highest adsorption efficiency of 43.28% for PP-Biochar and 49.19% for CC-Biochar. Both types of fabricated materials exhibited the fastest ammonium adsorption within the first 60 minutes. The ammonium adsorption capacities of CC-Biochar and PP-Biochar were 5.15 and 4.36 mg/g, respectively.